Analysis of Islamic Economic Law on Economic Rights of Domestic Violence Victims Wives in Indonesia 2020–2025 - Munawwir Ramadhan (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
Domestik Violence (DV) is one of the most massive human rights violations in Indonesia, especially economic violence against wives. It encompasses livelihood neglect, asset seizure, prohibition from working, and financial exploitation. The novelty of this study lies in the simultaneous integration of three analyzes covering that it has not been discussed in previous literature: (1) longitudinal statistical analysis of Komnas Perempuan's Annual Notes (CATAHU) 2020-2025, (2) normative reconstruction of Islamic Economic Law grounded in livelihood, al-milkiyyah al-mustaqillah, and maqashid al-syari'ah, and (3) comparative analysis with international human rights instruments (UDHR, ICESCR, CEDAW) and national positive law. The method uses normative legal research using statutory, conceptual, and comparative approaches. Findings reveal an increasing trend in economic violence cases from 680 (2020) to 5,942 (2025). Islamic Economic Law provides a strong normative foundation for protecting wives' economic rights, while the PKDRT Law has yet to deliver optimal economic recovery for victims. This study recommends regulatory harmonization based on Islamic Economic Law and Human Rights principles, strengthened livelihood enforcement through religious courts, and the establishment of an integrated economic protection fund for domestic violence victim wives.